2021
DOI: 10.5209/psic.77752
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Meaning-Centered Psychotherapy in adult patients with advanced cancer: A systematic review and meta-analysis

Abstract: Objective: We conducted a PRISMA-compliant systematic review of clinical trials, and a meta-analysis of randomised clinical trials (RCTs) of manualised Meaning-Centered Psychotherapy (MCP) interventions for adult advanced cancer patients. We searched seven databases for trials published in English and Spanish, until March 27, 2021. Results: Seven trials were included in the systematic review, and four in the meta-analysis. The systematic review favoured the effectiveness of MCP for the improvement of spiritual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
2
0
2
Order By: Relevance
“…The results found in this systematic review indicate that MCP is more effective than a control group with no active treatment (waitlist or psychoeducation group) (Bernstein et al, 2016;Cho et al, 2013;Delavari et al, 2014;Kim & Choi, 2020;Sun et al, 2021) and with a control group with CBT (Moosavi et al, 2012) in reducing depressive symptoms, improving meaning in life, and reducing anxiety in participants without physical illnesses, mainly in people who are going through difficult coping situations (caregivers), people who are in a life transition, such as the elderly after retirement, and patients diagnosed with major depressive disorder. Our results confirm those from previous meta-analyses that found MCP to be effective in reducing depression and anxiety in people with advanced cancer (Dietrich et al, 2021) and in improving meaning in life in people with physical illnesses (Vos et al, 2015;Vos, 2016;Vos & Vitali, 2018), and these results are consistent with the protective relationship between meaning in life and depressive symptoms found in previous studies (Huo et al, 2020;Marco, Alonso, & Baños, 2021;Marco, Cañabate, et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results found in this systematic review indicate that MCP is more effective than a control group with no active treatment (waitlist or psychoeducation group) (Bernstein et al, 2016;Cho et al, 2013;Delavari et al, 2014;Kim & Choi, 2020;Sun et al, 2021) and with a control group with CBT (Moosavi et al, 2012) in reducing depressive symptoms, improving meaning in life, and reducing anxiety in participants without physical illnesses, mainly in people who are going through difficult coping situations (caregivers), people who are in a life transition, such as the elderly after retirement, and patients diagnosed with major depressive disorder. Our results confirm those from previous meta-analyses that found MCP to be effective in reducing depression and anxiety in people with advanced cancer (Dietrich et al, 2021) and in improving meaning in life in people with physical illnesses (Vos et al, 2015;Vos, 2016;Vos & Vitali, 2018), and these results are consistent with the protective relationship between meaning in life and depressive symptoms found in previous studies (Huo et al, 2020;Marco, Alonso, & Baños, 2021;Marco, Cañabate, et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Second, Vos and Vitali (2018) conducted a meta‐analysis study and found 26 RCTs (16 studies with participants with cancer or physical illness and 10 studies with other psychological problems) that tested the effectiveness of MCP and found high improvements in quality of life (Hedges's g = 1.02) at post‐treatment and follow‐up; reductions in psychological stress (Hedges's g = 0.94); and improvements in meaning in life (Hedges's g = 1.18), hope and optimism (Hedges's g = .80), and self‐efficacy (Hedges's g = .89). Finally, Dietrich et al (2021) conducted an RCT meta‐analysis of MCP for adult participants with advanced cancer, and they found that, after the intervention, MCP showed high improvements in spiritual well‐being ( d = 0.52), quality of life ( d = 0.60) and depressive symptoms ( d = −0.50), a moderate effect on improving anxiety symptoms ( d = −0.47), and a low effect on reducing the desire for a quick death ( d = −0.28). Thus, the three meta‐analyses indicate that MCP could be an efficacious psychotherapy to reduce depression, stress, and increase meaning of life, improve quality of life in participants with chronic illness and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Günümüzde insanların anlam merkezli gereksinimlerini karşılamak için 28 farklı türde terapötik yaklaşım olduğundan bahsedilmektedir ve bu girişimler temelde bilişsel temelli olmakla birlikte varoluşsal yönelimlidir. Ortalama 6-9 seans süren ve bireylerin hastalık deneyimlerinden anlam bulmasına yardım edecek nitelikte yapılandırılmış, bireysel ya da grup olarak gerçekleştirilebilen girişimlerdir (21)(22)(23). Anlam odaklı terapilerin palyatif bakımda etkinliğini değerlendiren 3713 hastaya ait sonuçları (60 deneysel çalışma) inceleyen bir başka çalışma, yöntemin etkin olduğuna işaret etmektedir.…”
Section: Anlam Odaklı (Meaning-centered) Psikoterapilerunclassified
“…Hem terapinin hemen sonrası hem de izlem değerlendirmelerinde hastaların yaşam kalitesinde yükselme belirlenirken, yaşamda anlam bulmanın psikolojik stresi azaltmada aracı etkisi olduğu belirlenmiştir (21). Anlam odaklı terapilerin etkinliğini değerlendiren çalışma sonuçlarını irdeleyen iki meta analiz çalışması da hastaların yaşamlarında anlam bulma, manevi olarak iyi hissetme, yaşam kalitesini artırma, anksiyete ve depresyon belirtilerini azaltma ve fiziksel semptomların hafifletilmesinde anlamlı sonuçlar olduğundan bahsetmektedir (22,24). Rosenfeld ve ark'nın 124 hasta ile anlam odaklı ve 94 hasta ile destekleyici psikoterapi yürüterek, bu iki grubun sonuçlarını kıyasladıkları çalışmalarında anlam odaklı terapiler depresyon, yaşam kalitesi ve ölüm kaygısıyla başetmede destekleyici terapilere göre daha etkin bulunmuş ve terapötik faktörün "anlam" duygusu yaratmak olduğu belirlenmiştir (26).…”
Section: Anlam Odaklı (Meaning-centered) Psikoterapilerunclassified
“…Several previous research results that examined self-efficacy and art creation showed that the practical implications of social interaction between school, family, and culture have a psychosocial impact on the visual impairments manifested in art creation. Internal motivation and social support have a significant role in fostering social participation that can solve social realities, including self-confidence in producing works of art (Winkel et al, 2021;Dietrich, Estradé, & Cruzado, 2021;Ortiz-Peregrina et al, 2022). Depersonalization of the visual impairment group provides opportunities to create different results.…”
Section: Introductionmentioning
confidence: 99%